Studying strategy practices and strategy tools - Jarzabkowski, Paula (Henry Stewart Talks, 2012)
What are practices?, An S-as-P definition, Strategy practices, A strategy practice?, How to study them, Counting, Classifying, Intangibles, Strategy tools, Theorising practices, Sociomaterial, Classifying, describing, explaining, Steps forward